The Contribution of Regular Transportation Services, Government Subsidies, and the Optimization of Leverage and Liquidity in Enhancing Profitability for the Sustainability of Perum Damri - Ramdhani Agung Sukirno; Pudji Astuty; Sugiyanto Sugiyanto (Pelopor Publikasi Akademika, 2026)
Perum DAMRI, a State-Owned Enterprise (SOE) in the transportation sector, faces the challenge of balancing public service obligations (PSO) with financial sustainability. Empirical conditions indicate a high dependence on regular transportation revenue and government subsidies, alongside a relatively high leverage structure and vulnerable liquidity position. Ideally, the company is expected to achieve sustainable profitability with a sound financial structure. This discrepancy forms the basis for analyzing the determinants of profitability. This study aims to examine the simultaneous and partial effects of regular transportation revenue, government subsidies, leverage (Debt to Equity Ratio/DER), and liquidity (Current Ratio/CR) on profitability (Return on Assets/ROA). A quantitative approach with an explanatory method is employed using monthly time series data over an eight-year period (2017–2024), sourced from the audited financial and annual reports of Perum DAMRI. Data were analyzed using multiple linear regression with EViews 13, preceded by classical assumption tests and logarithmic transformation of revenue variables. The results show that all independent variables simultaneously have a significant effect on ROA (Prob(F-statistic) = 0.000000; R² = 0.7979). Partially, regular transportation revenue and government subsidies have a positive and significant effect, leverage (DER) has a significant negative effect, while liquidity (CR) has a positive and significant effect on profitability.